PENGEMBANGAN BUKU SUPLEMEN SISWA BERBASIS RECIPROCAL TEACHING PADA MATERI FLUIDA DINAMIS - Siti Ningrum; Nengah Maharta; Ismu Wahyudi (Jurnal Pembelajaran Fisika, 2017)
This research aims to produce student supplement book based on the reciprocal teaching of the Dynamic Fluid topic that is validated, attractive, easy, useful and effective. This research uses research and development research method with One Shot Case Study research design. The developed product was tested by an expert consisting of expert design test and expert test of the topic with good result and the product stated